Effects of Pulsed Nd:YAG Laser on Pt/Ag Thin Film Metal Contacts - Bhari, Bibi Zulaika; Ali, Ahmad Hadi (International Journal of Engineering and Technology, 2018)
This study focused on the effect of laser annealing on Pt/Ag metal contacts deposited on Silicon, (Si) substrates. DC sputtering was used to deposit the metal thin films on the Si. The samples were treated by annealing using pulsed Nd:YAG laser. Then, the samples were characterized based on its morphological, optical, structural and electrical properties. From surface morphological, it is clearly shown that the surface roughness of the laser annealed sample is smoother than the as-deposited sample. The calculated energy band gap was obtained as 1.38 eV. For electrical properties, the resistivity for laser anneal was lower compared to as-deposited sample, which are     5.10 × 10-4 ohm-cm and 1.37 × 10-3 ohm-cm respectively. The conductivity increases when the resistivity decreases.